Perlindungan Lingkungan dan Pembangunan Ibu Kota Negara (IKN) Dalam Tinjauan Hukum - Yanti Fristikawati; Nugroho Adipradana (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2022)
The development of new city, as well as the development of the new capital city of the Indonesia, will certainly have both positive and negative impacts. Some experts and NGOs assess that the development of the State Capital (IKN) will have a negative impact on the local community and the environment, but the government has made various efforts to reduce this adverse impact. This paper will discuss the pro and contra of IKN development, and what efforts have been made by the government and the existing regulations. The research method is a normative juridical method, which is a method that uses analysis from secondary data in the form of regulations and also expert opinions from books and journals. The government has made various efforts to protect the environment in the development of IKN, including making Law number 3 of 2022 concerning IKN. In addition, several other rules related to environmental protection will also be applied. The local government of East Kalimantan also has several regional regulations that can be applied to protect the environment in the development of IKN. It is hoped that with the application of appropriate rules and the efforts made by the government to protect the environment in the development of IKN.Keywords : Environmental protection, New Indonesian Capital